2003
DOI: 10.1149/1.1568108
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Structures in Electrodeposited Tin Base Negative Electrodes for Lithium Secondary Batteries

Abstract: Tin anodes deposited electrochemically on a copper foil current collector are studied to develop a next-generation lithium-ion battery with higher energy density. Better cycle performance through ten initial cycles under full charge and discharge conditions was attained by annealing tin electrodeposited on a rough surface copper foil. The annealing process was found to change the main active material from Sn to Cu6Sn5 with some minor compounds. Furthermore, a microcolumnar structure of the active material po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(59 citation statements)
references
References 25 publications
1
56
0
1
Order By: Relevance
“…Each of these coatings had a high porosity and a large surface area, which could be used as the electrodes for gas sensor [19] and Li-ion batteries [5,20]. It is also found that the ratio of Sn/SnO 2 can be easily controlled by simply and properly tuning the applied voltage, which can further enhance the properties of the deposits for the applications mentioned above.…”
Section: Resultsmentioning
confidence: 98%
“…Each of these coatings had a high porosity and a large surface area, which could be used as the electrodes for gas sensor [19] and Li-ion batteries [5,20]. It is also found that the ratio of Sn/SnO 2 can be easily controlled by simply and properly tuning the applied voltage, which can further enhance the properties of the deposits for the applications mentioned above.…”
Section: Resultsmentioning
confidence: 98%
“…87,[92][93][94] Take the compounds of Sn-based alloys as an example. Tamura et al 95 demonstrated that SnCu alloy plating on the Cu foil current collector can minimize volumetric changes by virtue of the formation of Cu 6 Sn 5 and Cu 3 Sn-like phases, and the rough surface of the Cu foil contributes to the stress relief among alloy micro-particles. The team later studied a Sn-Co alloy active composite attached on a Cu current collector which showed more desirable battery behavior.…”
mentioning
confidence: 99%
“…Tin is a promising anode material for lithium ion batteries because of its low charge potential and large theoretical capacity (991 mAh g -1 ) [8]. Although it is equivalent to about 2.5 times of the capacity of graphite, tin anode has limited application because of its large volume change up to 360 % in the process of alloying and dealloying of Li-Sn, which leads to pulverization and capacity fading [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%